Geneza chrześcijańskiej posługi hospicyjnej - Leśniewski, Krzysztof (Vox Patrum, 2018)
Hospice care to terminally ill people was originated due to a sensitivity to the personal dignity of man. Christianity brought a special contribution to the care of terminally ill people in the history of the world. Institutionalized Christian hospice care was started in the second half of the fourth century. The first hospices were founded in the Byzantine Empire and were destined for people suffering from leprosy. In the article there are stated the facts relating to the biblical foundations of the theology of diakonia and examples of the involvement of the hierarchy in the creation of hospitals according to the principles of Christian ethics. The Author underlines that the first Christian hospices have been an integral part of monasteries.